Radiotherapy versus observation after surgical resection of atypical meningiomas (2021)
Objectives: To describe the treatment and clinical results in patients diagnosed with atypical meningioma treated at the Donostia University Hospital. We evaluated recurrence, overall survival, and disease-free survival. Methods: From 284 meningiomas treated in our center over 16 years, 32 cases of grade II atypical meningioma were selected. Clinical and surgical notes were retrospectively evaluated. Pre and postoperative clinical and radiological parameters, the modality of radiotherapeutic treatment and its clinical results were evaluated. The histological classification was consistent with the 2007 WHO (World Health Organization) classification. The Simpson classification system was used to assess the degree of surgical resection. Results: we found 18 men and 14 women with a mean age of 60 years. Parasagittal location and convexity were the most frequent locations respectively (14 and 12 cases). The mean follow-up was 50 months. Simpson I-III resection was performed in 28 cases (87%). 22 patients (20 Simpson I-III and 2 Simpson IV) received postoperative radiotherapy (20 cases fractionated radiotherapy and radiosurgery in 2), while 10 patients (8 Simpson I-II and 2 Simpson IV) did not receive postoperative radiotherapy. The recurrence rate in patients who received radiotherapy was 45% and 60% in those who did not receive radiotherapy. Recurrence-free survival and overall survival in patients under radiotherapy was 36 and 48 months, respectively. On the contrary, in those who did not receive radiotherapy it was 44 and 56 months. Conclusions: In this study, the most important prognostic factor related to survival was the degree of surgical resection. Therefore, adjuvant radiotherapy should be used in those cases without complete surgical resection. In addition, we recommend evaluating reoperation in recurrent symptomatic cases. © 2021 The Authors